Conflitos sociais e afirmação territorial da comunidade quilombola Ilha São Vicente, Araguatins, Tocantins - Ricardo Gilson da Costa Silva; Luciano Laurindo dos Santos; Jorlando Ferreira Rocha; Luziane Laurindo dos Santos; Cristiano Bento da Silva (Confins)
The quilombola community São Vicente Island is located in the municipality of Araguatins, state of Tocantins, in Brazil. It was recognized by the Palmares Cultural Foundation (FCP) in 2010. In this work, we intend to analyze the socio-historical processes that formed the remaining quilombo communities, from slavery to community organization on São Vicente Island, their means of collective production in their territory and the contemporary challenges they face. It is a horizontal analysis of the molecular processes that configure the territory and territorialities of the quilombola community.